When we find the derivative of xn, we use the formula
d(xn)/dx = nxn-1
Find dy/dx if :
Problem 1 :
y = x + √x
Solution :
y = x + √x
y = x1 + x1/2
Using the Power rule of derivative,
dy/dx = 1x0 + (1/2) x(1/2 - 1)
= 1(1) + (1/2) x-1/2
= 1 + 1/2x1/2
dy/dx = 1 + 1/2√x
Problem 2 :
y = x5 - 3√x
Solution :
y = x5 - 3√x
y = x5 - 3x1/2
Using the Power rule of derivative,
dy/dx = 5x4 - (1/2) 3x(1/2 -1 )
= 5x4 - (1/2) 3x-1/2
= 5x4 - 3/2x1/2
dy/dx = 5x4 - 3/2√x
Problem 3 :
y = x5/2 - 2/x
Solution :
y = x5/2 - 2/x
y = x5/2 - 2x-1
Using the Power rule of derivative,
dy/dx = 5/2 x(5/2 - 1) - 2(-x-1 - 1)
= 5/2 x3/2 + 2x-2
dy/dx = 5/2 x3/2 + 2/x2
Problem 4 :
y = 3x4 - 2/x + 6/x2
Solution :
y = 3x4 - 2/x + 6/x2
y = 3x4 - 2x-1 + 6x-2
Using the Power rule of derivative,
dy/dx = 12x3 - 2(-x-1 -1 ) + (-12x-2 - 1)
= 12x3 + 2x-2 - 12x-3
dy/dx = 12x³ + 2/x² - 12/x³
Problem 5 :
y = (x + 5) (x + 2)
Solution :
y = (x + 5) (x + 2)
y = x² + 2x + 5x + 10
y = x² + 7x + 10
Using the Power rule of derivative,
dy/dx = 2x + 7
Problem 6 :
y = (3x + 1) (5x - 3)
Solution :
y = (3x + 1) (5x - 3)
y = 15x² - 9x + 5x - 3
y = 15x² - 4x - 3
Using the Power rule of derivative,
dy/dx = 30x - 4
Problem 7 :
y = (5x² - 3) (4x³ + x)
Solution :
y = (5x² - 3) (4x³ + x)
y = 20x5 + 5x3 - 12x3 - 3x
Using the Power rule of derivative,
dy/dx = 100x4 + 15x² - 36x² - 3
dy/dx = 100x4 - 21x2 - 3
Problem 8 :
y = (x3 + 1) (2x + 3)
Solution :
y = (x3 + 1) (2x + 3)
y = 2x4 + 3x3 + 2x + 3
Using the Power rule of derivative,
dy/dx = 8x3 + 9x2 + 2
Problem 9 :
y = (x5 - 2x)2
Solution :
y = (x5 - 2x)2
y = (x5 - 2x) (x5 - 2x)
y = x10 - 2x6 - 2x6 + 4x2
y = x10 - 4x6 + 4x2
Using the Power rule of derivative,
dy/dx = 10x9 - 24x5 + 8x
Problem 10 :
y = (x - 2) (x + 1) (3x + 1)
Solution :
y = (x - 2) (x + 1) (3x + 1)
y = x(x + 1) (3x + 1) - 2(x + 1) (3x + 1)
y = x(3x² + x + 3x + 1) - 2(3x² + x + 3x + 1)
y = 3x³ + x² + 3x² + x - 6x² - 2x - 6x - 2
y = 3x³ - 2x² - 7x - 2
Using the Power rule of derivative,
dy/dx = 9x² - 4x - 7
Problem 11 :
y = (x - a)³
Solution :
y = (x - a)³
By using binomial formula,
(a - b)³ = a³ - 3a²b + 3ab² - b³
y = x³ - 3x²a + 3xa² - a³
Using the Power rule of derivative,
dy/dx = 3x² - 6xa + 3a²
Problem 12 :
y = (2x + 3)³
Solution :
y = (2x + 3)³
By using binomial formula,
(a + b)³ = a³ + 3a²b + 3ab² + b³
y = (2x)³ + 3(2x)²(3) + 3(2x)(3)² + 3³
y = 8x³ + 36x² + 54x + 27
Using the Power rule of derivative,
dy/dx = 24x² + 72x + 54
Problem 13 :
y = 2x (3x² - 7x + 8)
Solution :
y = 2x (3x² - 7x + 8)
y = 6x³ - 14x² + 16x
Using the Power rule of derivative,
dy/dx = 18x² - 28x + 16
Problem 14 :
y = 3x² (x + 1) (x - 2)
Solution :
y = 3x² (x + 1) (x - 2)
y = 3x² (x² - 2x + x - 2)
y = 3x² (x² - x - 2)
y = 3x4 - 3x³ - 6x²
Using the Power rule of derivative,
dy/dx = 12x³ - 9x² - 12x
Problem 15 :
y = (x + 1/x)²
Solution :
y = (x + 1/x)²
By using binomial formula,
(a + b)² = a² + b² + 2ab
y = x² + (1/x)² + 2x(1/x)
y = x² + 1/x² + 2
y = x² + x-2 + 2
Using the Power rule of derivative,
dy/dx = 2x + (-2)x(-2 - 1)
= 2x - 2x-3
dy/dx = 2x - 2/x3
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM